Management Of Jigsaw Model To Increase Student Interest In Motorization Courses - Siagian, Fera Ratna Dewi; Petrus Agustinus Franco Kapitan; Ratno Susanto (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2024)
The purpose of this study is to explore how the application of the jigsaw model in motor courses can affect student interest and understanding. The results of this study are expected to provide insight into more effective teaching methods for complex material. This research method uses a qualitative approach. Data analysis techniques in this study used descriptive and statistics. The data obtained in the form of questionnaires and student learning outcomes were analyzed to determine the effectiveness of learning and differences in student learning outcomes. The results obtained from the physical fitness test of motor course participants of Physical Education Students of Nusa Cendana University are included in the good category, with a total percentage of 61.6%. Thus, the results showed that most of the participants of the sports motor course at the University of Nusa Cendana Physical Education had a moderate level of learning. However, the endurance component must be further improved by increasing the learning time. With this, motor course lecturers are given advice to increase the duration of learning, so that motor course participants are maximized in doing exercises and make it easier for sports motor course participants to improve student academic achievement.